Pathophysiological consequences and benefits of HFE mutations: 20 years of research - Hollerer, Ina; Bachmann, André; Muckenthaler, Martina (Haematologica, 2017)
Mutations in the HFE (hemochromatosis) gene cause hereditary hemochromatosis, an iron overload disorder that is hallmarked by excessive accumulation of iron in parenchymal organs. The HFE mutation p.Cys282Tyr is pathologically most relevant and occurs in the Caucasian population with a carrier frequency of up to 1 in 8 in specific European regions. Despite this high prevalence, the mutation causes a clinically relevant phenotype only in a minority of cases. In this review, we summarize historical facts and recent research findings about hereditary hemochromatosis, and outline the pathological consequences of the associated gene defects. In addition, we discuss potential advantages of HFE mutations in asymptomatic carriers.
Gesehen am 23.08.2018